2015
DOI: 10.1111/acfi.12133
|View full text |Cite
|
Sign up to set email alerts
|

Investment–cash flow sensitivity measures investment thirst, but not financial constraint

Abstract: Literature streams disagree about the capacity of investment-cash flow sensitivity (ICFS) to measure both investment thirst and financial constraint. We argue that ICFS measures the former but not the latter. Therefore, we use Fazzari et al. 's study (1988) to develop a model to test the relationship between ICFS and financial constraint, but extend that model using Kornai (1979) to include investment thirst. We demonstrate: because the ICFS-financial constraint relationship varies, ICFS cannot measure financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
(82 reference statements)
1
8
0
1
Order By: Relevance
“…The extant literature suggests that the government benefits that accrue to a firm with PC enhance firm value. We also show direct evidence that Chinese firms actively build PC (the benefits of PC outweigh its costs, therefore, a positive 3 See Chen and Chen (2012) and Deng et al (2015) for a discussion of the use of the WW index and the SA index. We also detail how these indices are constructed in Appendix S2.…”
Section: Literature Reviewmentioning
confidence: 68%
“…The extant literature suggests that the government benefits that accrue to a firm with PC enhance firm value. We also show direct evidence that Chinese firms actively build PC (the benefits of PC outweigh its costs, therefore, a positive 3 See Chen and Chen (2012) and Deng et al (2015) for a discussion of the use of the WW index and the SA index. We also detail how these indices are constructed in Appendix S2.…”
Section: Literature Reviewmentioning
confidence: 68%
“…In particular, when these have been proxied by means of an indirect measure obtained from secondary data (especially when amount of cash flow has been used as a proxy of internal funds available), the results have been quite mixed. Indeed, some studies [30,31] have suggested significant cash flow sensitivity in companies' investment decisions, while others [32,33] have provided evidence of the opposite. In contrast, when financial criticalities have been investigated by employing a direct measure (i.e., ad hoc surveys designed to collect companies' views on barriers to funding their investment projects), the results have seemed to univocally support the existence of financial constraints hindering firms' investment behavior.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Credit-expansion policies may also confound our results on the tax-leverage effect. In November 2008, the Chinese central government unexpectedly announced an economic stimulus package of four trillion RMB (seeDeng, Ding, Zhu, & Zhou, 2017). At the time, this was equivalent to 586 billion USD and represented about 16% of China's annual GDP.…”
mentioning
confidence: 99%